Investment Feasibility Analysis of LPG Bulk Filling Station (SPBE): Improving LPG Distribution in The City of Sorong - Indra Hidayat (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
LPG Bulk Filling Station ("SPBE") is a facility for bottling LPG (Liquefied Petroleum Gas) gas into 3 Kg, 5 Kg, 12 Kg or 50 Kg cylinders with the LPG brand. SPBE is an important facility in the LPG distribution network in Indonesia. The purpose of this study is to identify the potential LPG market in Sorong and its surroundings and conduct a feasibility study on the construction of SPBE facilities in the Sorong SEZ. The methods used are quantitative and qualitative using secondary data using a market sizing approach to identify LPG market potential using data from the Directorate General of Oil and Gas of the Ministry of Energy and Mineral Resources and data from the Central Statistics Agency (BPS). Furthermore, a financial feasibility formulation was made to determine the business feasibility of SPBE infrastructure development and sensitivity analysis using the Monte Carlo approach for 10,501 iterations. And the study ended with a risk analysis using a risk register to map possible risks and how to deal with and handle them. The results of the study show that the development of SPBE infrastructure in the Sorong SEZ is feasible to be built with feasibility indicators in the form of IRR (Internal Rate of Return) of 12.79%; NPV (Net Present Value) of IDR 2,479,320,100; PI (Profitability Index) of 1.18; and DPP (Discounted Payback Period) for 12.34 years with a record average total LPG consumption of 9.81 tons/day in Sorong in a realistic scenario. Meanwhile, in an optimistic scenario with an average total LPG consumption of 11.07 tons/day, the feasibility indicator is an IRR of 14.995; NPV of IDR 4,726,461,323; PI from 1.34; and DPP for 10.48 years. The construction of SPBE infrastructure requires a cost of IDR 11,189,458,937 with a compact type of SPBE infrastructure with a land area of 60 m x 40 m or an area of 2,400 m2